2004
DOI: 10.1016/j.vaccine.2004.02.034
|View full text |Cite
|
Sign up to set email alerts
|

Differential efficacy of vaccinia virus envelope proteins administered by DNA immunisation in protection of BALB/c mice from a lethal intranasal poxvirus challenge

Abstract: DNA vaccines might offer an alternative to the live smallpox vaccine in providing protective efficacy in an orthopoxvirus (OPV) lethal respiratory challenge model. BALB/c mice were immunised with DNA vaccines coding for 10 different single vaccinia virus (VACV) membrane proteins. After an intranasal challenge with the VACV IHD strain, three gene candidates B5R, A33R and A27L produced ≥66% survival. The B5R DNA vaccine consistently produced 100% protection and exhibited greatest efficacy after three 50 g intram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
63
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 24 publications
1
63
0
Order By: Relevance
“…Antibodies directed against A27L have potent IMV-neutralizing capacity in vitro (27). Intraperitoneal immunization of mice with Escherichia coli-expressed A27L protein or passive treatment with A27L-specific monoclonal antibodies provides full protection against lethality in a vaccinia virus challenge model (8,27,38), while a DNA vaccine encoding A27L offers partial protection (35). In addition to humoral responses, in vitro restimulation with A27L elicits cellular proliferative immune responses in splenocytes isolated from vaccinia virus-infected mice (8).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Antibodies directed against A27L have potent IMV-neutralizing capacity in vitro (27). Intraperitoneal immunization of mice with Escherichia coli-expressed A27L protein or passive treatment with A27L-specific monoclonal antibodies provides full protection against lethality in a vaccinia virus challenge model (8,27,38), while a DNA vaccine encoding A27L offers partial protection (35). In addition to humoral responses, in vitro restimulation with A27L elicits cellular proliferative immune responses in splenocytes isolated from vaccinia virus-infected mice (8).…”
mentioning
confidence: 99%
“…In vitro, antibodies directed against D8L have IMV-neutralizing activity, and soluble D8L protein inhibits the adsorption of wild-type vaccinia virus to cells (23). In vivo, D8L is immunogenic, and immunization of mice with a DNA vaccine encoding D8L provides partial protection from lethal vaccinia virus challenge (35). A recent study by Sakhatskyy et al has confirmed that D8L induces strong protective antibody responses in vivo and improves the efficacy of polyvalent poxvirus DNA vaccines composed of A27L and B5R or of A27L, B5R, L1R, and A33R (41).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…While the current licensed live vaccinia virus-based vaccine is extremely effective [3] and results in remarkably long-lived immune responses (e.g., [4]), it has an unacceptable safety profile [5,6] for wide use when considered in today's setting of global eradication of active smallpox disease. Approaches to develop safer smallpox vaccines have ranged from the study of more attenuated live vaccinia viruses (such as MVA [7][8][9] or LC16m8 [10,11]) to subunit vaccines that rely on specific viral targets delivered either as DNA plasmids [12][13][14][15] or purified proteins [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%